Catálogo para dispositivos móveis - Motta, Robson da (2014)
This paper talks about the issue of developing a system that provides an alternative to product catalogs. Conventionally these catalogs are printed in large quantity, which generates volumes and costs for companies that work with these products. The development of the system proposes the integration of the environment of the internet with the mobile, which is conducted through the WebService. The preparation of both systems is by means of the Java programming language, it is used to development of the web system, and of the mobile application available in Android platform. The Web Service, in turn, performs the integration through the REST and JSON technologies to provide the transport of information between the different environments, providing simplicity and speed during the request procedure of the mobile application.